Recycling of wood fiber‐reinforced HDPE by multiple reprocessing. Issue 35 (19th May 2016) - Åkesson, Dan; Fuchs, Torsten; Stöss, Michael; Root, Andrew; Stenvall, Erik; Skrifvars, Mikael
ABSTRACT: The mechanical recycling of high‐density polyethylene (HDPE) reinforced with wood fiber was studied by means of repeated injection moulding. The change in properties during the recycling was monitored by tensile and flexural tests, Charpy impact tests, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), FTIR spectroscopy, and by measuring the fiber lengths. Tests were also done where injection moulding was combined with subsequent accelerated thermo‐oxidative ageing and thereafter repeated numerous times. The results showed that the HDPE composites were relatively stable toward both the ageing conditions and the repeated injection moulding. The change of the mechanical properties was mainly observed as an increased elongation at max. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43877. Abstract :